2005
DOI: 10.1021/cm050271e
|View full text |Cite
|
Sign up to set email alerts
|

A New Route to Monolithic Methylsilsesquioxanes:  Gelation Behavior of Methyltrimethoxysilane and Morphology of Resulting Methylsilsesquioxanes under One-Step and Two-Step Processing

Abstract: Polymerization of methyltrimethoxysliane (MTMS) results in methylsilsesquioxane (MSQ), which has found important applications in recent years including use as low-k dielectric materials in the semiconductor industry, superhydrophobic materials, monolithic columns, and hybrid matrixes for immobilizing proteins. For polycondensation of MTMS in ethanolic solutions, we report the sol-gel behavior under two different sets of conditions. First, we examined one-step polymerization over a wide range of pH and show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
95
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 53 publications
1
95
0
Order By: Relevance
“…The ESEM image of the gel prepared in methanol demonstrates rough structure consisting of micrometre sized particles indicating phase separation, which is in accordance with a previous report. 26 On the other hand, the ESEM image of the gel prepared by using DMSO as solvent shows smooth surface (gel network was further characterized with SEM and TEM after drying and given below) indicating homogeneous gel formation without phase separation. Homogeneous MSQ gel formation in DMSO demonstrates that all species formed during polymerization can effectively dissolve in the system.…”
Section: Preparation Of Transparent Msq Gelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ESEM image of the gel prepared in methanol demonstrates rough structure consisting of micrometre sized particles indicating phase separation, which is in accordance with a previous report. 26 On the other hand, the ESEM image of the gel prepared by using DMSO as solvent shows smooth surface (gel network was further characterized with SEM and TEM after drying and given below) indicating homogeneous gel formation without phase separation. Homogeneous MSQ gel formation in DMSO demonstrates that all species formed during polymerization can effectively dissolve in the system.…”
Section: Preparation Of Transparent Msq Gelsmentioning
confidence: 99%
“…The gels are surprisingly homogeneous instead of the commonly obtained macroscopic phase separated MSQ gels when prepared in alcohols by using the same precursor. [25][26][27] This is because all structures formed during polymerization are dissolved in DMSO. Here, for the first time, we prepared uniform and nanoporous thin films by using homogeneous MSQ gels.…”
Section: Introductionmentioning
confidence: 99%
“…1. In either sample, the mass decrease due to the exothermic decomposition of SiCH 3 group was observed from 300 to 500°C, 15), 16) and there was no indication of the other phases than co-polymerized DMDMS and MTMS. It shows a reasonable agreement with the results shown in Fig.…”
mentioning
confidence: 93%
“…25), 26) In particular, it is crucial to enhance the contact between analyte molecules and pore surface by an adequate control of these pores for better separation functions in separation media for high-performance liquid chromatography (HPLC). 25),27) We 15) and Dong et al 28) reported the preparation of PMSQ materials with well-defined macropores that are characterized by co-continuous structure formed through polymerization-induced phase separation in parallel with solgel transition in the absence of surfactant, though the hierarchically macro-mesoporous PMSQ was found to be challenging. Instead, Dong et al obtained PMSQ monolithic gels only with mesopores without template in the same synthetic framework, which is similar to the "non-templated" silica gels with interstices between colloidal constituents, though the con-trollability of mesopore size was limited and no hierarchically porous PMSQ has been reported in these papers.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, Dong et al obtained PMSQ monolithic gels only with mesopores without template in the same synthetic framework, which is similar to the "non-templated" silica gels with interstices between colloidal constituents, though the con-trollability of mesopore size was limited and no hierarchically porous PMSQ has been reported in these papers. 28), 29) In contrast to the silica systems, 25),30) the lack of strong attractive interactions as described above makes the introduction of mesopores in such phase separation systems unrealistic. Alternatively, mesopores may be formed as interstices between gel colloids in the macropore skeletons in the phase separation systems.…”
Section: Introductionmentioning
confidence: 99%